2006
DOI: 10.1159/000094787
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hepatitis C and Crohn’s Disease: Nosocomial Infection Treatment with PEG-Interferon plus Ribavirin

Abstract: We describe the case of a patient with a diagnosis of Crohn’s disease and accidental infection during abdominal surgery by hepatitis C virus (HCV) who received combination therapy with pegylated interferon-α2b (1.5 µg/kg weekly) plus ribavirin (10.6 mg/kg daily) for histologically demonstrated chronic hepatitis C. After 48 weeks treatment, serum transaminase levels were normal and viremia (HCV RNA) was negative (end-of-treatment response); 24 weeks later (follow-up period), a sustained virological response was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…On the other hand, 6 case reports with a favorable IBD outcome while on treatment with IFN-α with or without ribavirin were found on literature review 22, 31–35 . All cases were on IBD maintenance therapy during antiviral treatment and no flares were documented.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, 6 case reports with a favorable IBD outcome while on treatment with IFN-α with or without ribavirin were found on literature review 22, 31–35 . All cases were on IBD maintenance therapy during antiviral treatment and no flares were documented.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the late 1990s, patients with IBD were considered to be at risk of HCV and HBV infection, probably due to previous surgery or blood transfusions. [1][2][3][4][5] Prevalence of HBV infection Some relatively 'old' studies have reported a significantly higher prevalence of HBV infection in IBD patients than in controls. For example, Biancone et al 2 reported that 11% of IBD patients had antibodies to hepatitis B core protein (anti-HBc), a statistically significantly higher figure than in controls.…”
Section: What Is the Prevalence Of Hbv And Hcv Infection In Ibd Patiementioning
confidence: 99%
“…16,117,118 Nevertheless, this recommendation remains controversial, as other authors could not confirm the negative effect of inter-feron-a in patients with CD. 2,4,48,56 Scherzer et al 62 analysed the tolerability of interferon-a plus ribavirin in patients with chronic HCV infection and CD, and concluded that gastrointestinal symptoms may be temporarily exacerbated (6 of the 11 CD patients experienced exacerbation of CD-related symptoms). Nevertheless, increased CD activity is easily managed with short-term medical (glucocorticoid) therapy.…”
Section: What Is the Risk Of Exacerbation Of Ibd With Interferon?mentioning
confidence: 99%
“…As a result of the over expression of Th‐1‐related proinflammatory cytokines including IFN‐γ and TNF‐α, 37 antiviral HCV treatment with IFN‐alpha may induce CD activity. A few case reports describe IBD flares in patients under IFN‐alpha treatment, 17–22 but others observed no increase in CD activity on treatment with IFN‐alpha with or without ribavirin 23, 25, 26 . One patient was successfully treated with pegylated IFN‐alpha and ribavirin on infliximab treatment 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, gastroenterologists are reluctant in treating IBD patients with IFN‐alpha. Only a few case reports of successfully treated IBD/HCV patients have been published, using various older 23, 24 or current standard regimes using pegylated IFN‐alpha and ribavirin 25, 26 …”
Section: Introductionmentioning
confidence: 99%